Bd. Breast Pain Reduction Techniques Using Cabbage Leaves - Uswatun Kasanah; Ana Rofika; Eviyati Aini Muriana; Irfana Tri Wijayanti; Retno Wulan; Iin Tri Marlinawati (Jurnal Penelitian Pendidikan IPA, 2026)
Breast pain and engorgement are common problems experienced by postpartum mothers and may interfere with successful breastfeeding. One non-pharmacological method that has been widely used to relieve breast discomfort is the application of cabbage leaf compresses. This study aimed to analyze the differences in breast pain levels among breastfeeding mothers who received cabbage leaf compresses compared to those who did not. A quasi-experimental study was conducted at Jakenan Health Center, Indonesia, in May to September 2024. The study involved postpartum mothers on days 2–4 after delivery who were selected using a consecutive sampling technique. Breast pain levels were measured before and after the intervention. Data normality was assessed using the Shapiro–Wilk test, and differences between groups were analyzed using the Mann–Whitney test with a 95% confidence interval. The results showed a significant difference in breast pain levels between the intervention group and the control group. Mothers who received cabbage leaf compresses experienced a greater reduction in breast pain than those who did not receive the intervention (p = 0.005). In conclusion, cabbage leaf compresses are effective in reducing breast pain among postpartum mothers and may be considered a simple, safe, and affordable intervention to support breastfeeding